Excellence in Language Education (Journal of the College of Education for Women, 2019)
The primary goal of the study is to practise some systematic strategies for foreign language instruction despite the fact that no single approach to language classroom instruction is inherently superior to others; instead the choice of an approach should be determined by the teacher, students, the subject matter, and the situation. The paper adopts certain strategies which may assist EFL teachers to excel in their work and continue their professional development. Hence, it is intended for language teachers who understand the value of good teaching and like to produce academically successful students. The study could also help college student teachers to acquire new strategies in order not only to succeed but also to excel in their learning and future career.